Upaya guru dalam mengelola perilaku hiperaktif di Kelas: studi deskriptif kualitatif - Nugraha, Radhyka Putra; Wikansari, Amanati; Dewanti, Shevi Amrilla; Anggraeni, Delia Eka; Prabowo, Sidig Nur; Haningsih, Sri; Qurdani, Farhan Alul; Hanifah, Suko Nur; Ramadhani, Dhea; Ernawati, Sari; Manungsong, Feny Theresia (Literal: Disability Studies Journal, 2024)
This research is motivated by the existence of hyperactive behavior that still exists in elementary schools. This is where the role of teachers in learning hyperactive children is very necessary. The aim of this research is to describe the behavior of hyperactive children, teachers' efforts in guiding hyperactive children and the obstacles faced in guiding hyperactive children. This type of research is descriptive qualitative research, namely research that attempts to describe symptoms, events, events that have occurred. The data sources for this research are class teachers, classmates, hyperactive children. The data collection techniques used in this research are observation, interviews and documentation. The data analysis technique used is qualitative data analysis starting from data reduction, data presentation, and drawing conclusions. The result shows that  the behavioral characteristics of hyperactive children at SD Negeri 3 Kotagede include not being able to stay still, often throwing tantrums, not paying attention to teachers, often disturbing friends, and being easily distracted. The efforts made by teachers in dealing with hyperactive children at SD Negeri 3 Kotagede are that when they are concentrating the teacher will help the student's learning and continue to monitor them. When learning, the teacher applies cooperative learning strategies, namely in groups. Further studies are needed to find the best method to overcome the negative impact of hyperactivity in elementary schools.